The Impact of Bank Credit on the Libyan GDP During the Period 1995-2020, An Applied Study on Libyan Commercial Banks - Sharanna, Murad Milad; Al-Abdi, Faraj Mansour (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The aim of this research is the ability of commercial banks to use deposits as a political resource to finance their credit and investment activities. We started with the first step, which is the preliminary study. Deposits Hence, commercial banks encourage credit and savings operations. Then comes the second step in the work of commercial banks, which is the credit activity, then the process of granting loans, and then we moved to the analytical study and found that commercial banks are subject to the supervision of the Central Bank, and therefore the Central Bank has proven its existence. The results of the standard model for the effect of the relationship between bank credit and GDP showed that it is positive, significant and compatible with the foundations of economic theory, as the higher the volume of bank credit and loans granted by commercial banks, the more the various economic sectors increase the volume of investment and thus the gross domestic product increases. The results of flexibility showed that the higher the bank credit by 1%, the higher the gross domestic product by 83%, which is a weak percentage, meaning that the output does not respond to the increase in bank credit at high rates despite the increase in bank credit, and the reason for this is due to the inefficient use in industrial projects Agricultural and service sectors are economically and financially feasible.